Improving sweet sorghum for enhanced juice traits and biomass. (22nd October 2019) - Bandara, Ananda Y.; Weerasooriya, Dilooshi K.; Gobena, Dereje D.; Hopper, Daniel J.; Tesso, Tesfaye T.; Little, Christopher R.
Abstract: Sweet sorghum ( Sorghum bicolor [L.] Moench) is a prospective bioethanol feedstock source. Four high‐biomass and sweet sorghum male lines and three grain sorghum female lines were intercrossed using Design II mating. Parents and hybrids were evaluated to (a) identify genetic sources to improve biofuel traits, and (b) determine the inheritance of biofuel and morpho‐agronomic traits. Total soluble sugars (TSS) per plant were determined using juice weight (JW) and Brix (°Bx). Plant height (PH), biomass (BM) and stalk diameter ( SD ) were also measured. Mean hybrid performance for PH, JW, TSS and BM was higher than the male parent means. Three male parents exhibited positive and significant general combining ability (GCA) for at least three traits. Among males, PI185672 showed the highest GCA for PH, °Bx and BM, while No. 08 exhibited the greatest GCA for JW and TSS. Most hybrids exhibited overdominance‐driven high‐parent heterosis for all traits except SD . Trait broad‐sense heritability ranged from 0.71 (BM) to 0.93 (PH). Results revealed that biofuel traits could be substantially improved through breeding, which will contribute to enhanced bioethanol production.